Menerjemahkan Instrumen Preterm Infant Breastfeeding Behavior Scale ke Bahasa Indonesia: Studi Pilot - Shiyanatilmaula, Ulis; Purwandari, Haryatiningsih; Rahmawati, Eni (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2023)
Background:The availability of instruments to observe the behavior of premature infants while breastfeeding in Indonesia is important, considering the number of premature babies in Indonesia is high Indonesia Objective: This study aims to translate and cross-cultural adaptation of the Preterm Infant Breeding Behavior Scale (PIBBS) into Indonesian. Methods: The research design uses instrument translation, including testing the reliability of the instrument. The study was conducted by observing 10 breastfeeding sessions on a convenience sample of three late preterm infants (34-<37 weeks' gestation) and mothers in the Perinatology Room of RSUD Goeteng Taroenadibrata. Observations were made by the researcher and the baby's mother. The research instrument used a demographic sheet, and PIBBS. The inter-rater reliability test was carried out using the percentage agreement on observations and the Intraclass Correlation Coefficient (ICC). Research Results: The study found the percentage agreement on the observation of premature babies' behavior while breastfeeding was 80-100%. Intraclass Correlation Coefficients (ICC) observations of nipple seeking behavior, areola coverage, attachment and attachment to the breast, nipple sucking, longest sucking burst, and swallowing behavior were >0.90, 1.00, 1.00, 1.00, >0.90, and 1.00. Conclusion: The Indonesian version of the PIBBS instrument has a very good reliability value. This instrument is appropriate and can be used to observe the behavior of premature babies while breastfeeding in Indonesia